How aviation deregulation promotes international tourism in Northeast Asia: A case of the charter market in Japan. (October 2016) - Wu, Chuntao
Highlights: This study explores the effects of charter promotions on international tourism in Japan. Charter promotion stimulated tourism development in regional areas. Regular flights deregulation led to a decline in charters but not in all regions. New charter destinations benefited from subsidy package, target market and innovation measure. Charters business is an independent sector based on market demand now.